Effect of coronavirus disease 2019 pandemic on the lifestyle and glycemic control in patients with type 2 diabetes : a cross-section and retrospective cohort study - Chihiro Munekawa; Yukako Hosomi; Yoshitaka Hashimoto; Takuro Okamura; Fuyuko Takahashi; Rena Kawano; Hanako Nakajima; Takafumi Osaka; Hiroshi Okada; Saori Majima; Takafumi Senmaru; Naoko Nakanishi; et al. (ENDOCRINE JOURNAL, 2021)
[Abstract.] To investigate the acute effects of the coronavirus disease 2019 (COVID-19) on the lifestyle and metabolic parameters in patients with type 2 diabetes mellites. This cross-sectional and retrospective cohort study induced 203 patients who completed a questionnaire regarding stress levels and lifestyles. Data regarding stress levels, sleep time, exercise, and total diet, snack, and prepared food intake were obtained from the questionnaires. The changes in the body weight or HbA1c levels were determined by comparing the values at the time the questionnaire was administered to those noted 3 months ago. Increased levels of stress and decreased exercise levels were reported in approximately 40% and >50%. During the COVID-19 pandemic. There was a negative correlation between stress and exercise (r=-0.285, p<0.001) and a positive correlation between stress and prepared food intake (r=0.193, p=0.009). Decreased exercise levels (r=-0.33, p<0.001) and increased snack consumption (r=0.24, p=0.002) were associated with increased body weight. Furthermore, increased total diet intake (r=0.16, p=0.031) was associated with increased HbA1c levels. These relationships remained significant for patients aged <65 years and patients who did not engage in regular exercise. Many patients experienced stress and lifestyle changes due to the COVID-19 pandemic, and these changes were associated with increased body weight and HbA1c levels.